Medio siglo de docencia - Oroz, Rodolfo (Revista Chilena de Humanidades, 2015)
The author outlines the highlights of his academical life as a contemporaryof outstanding professors at the University of Chile. He mentions his effortswithin the fields of investigation and teaching of Philology and Linguistics,emphasizing the relation between words and man's view of his outer world.Lastly, he ratifies the importance of investigation, remembering that the fame ofa university is based mainly on the scientific reputation of its academic staff